Facial Plastic Surgery in Pediatric Otolaryngology: Outcomes and Satisfaction. (2nd September 2014) - Vincent, Richard L.; Pereira, Kevin D.; Ambro, Bryan T.
Abstract : Objectives: Highlight the role of facial plastic and reconstructive surgery in the surgical management of pediatric head and neck lesions and assess cosmetic outcomes. Methods: Retrospective case series of 13 pediatric head and neck lesions managed at a tertiary care children's hospital. The charts of all patients were reviewed for clinical presentation, radiologic findings, surgical technique used for excision and reconstruction, preoperative and postoperative photography, pathology and cosmetic outcomes. Results: A total of 13 pediatric patients with ages ranging from 18 months to 12 years had adequate documentation for review. There were 4 naso‐frontal dermoids, 4 head and neck skin lesions, 3 midface/orbital bony lesions, and 2 parotid/facial soft tissue lesions. Six patients were managed by soft tissue advancement flaps, 2 required complex linear closure and 2 had a surgical exposure achieved with cosmetically placed incisions. Two patients needed a midface degloving approach for exposure, one required medial osteotomies and bone pate for reconstruction and 2 were managed with calvarial bone grafts. At last follow‐up cosmetically acceptable outcomes were photographically documented in all 13 patients. This was confirmed by parental satisfaction. Conclusions: The involvement of facial plastic and reconstructive surgery is an important adjunct in the management of pediatric head and neck lesions. It leads to better cosmetic outcomes that can be documented and confirmed by parental satisfaction.